2013
DOI: 10.4161/cc.25508
|View full text |Cite
|
Sign up to set email alerts
|

FKBPs and the Akt/mTOR pathway

Abstract: PersPeCtives 2366Cell Cycle volume 12 issue 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…However, FKBP-rapamycin/rapalog complex mediated mechanism of mTOR function inhibition can be de facto the substantial source of the numerous off-target effects. FKBPs (of different molecular mass 12, 12.6, 13, 25, 51, and 52kDa) are the members of the family of peptidylprolyl cis/trans isomerases and strong binders of rapamycin Hausch et al, 2013). Besides their potential to form rapamycininduced ternary complexes with mTOR and hinder mTOR kinase substrate accessibility, the each member of this family has the diverse binding partners (Erlejman et al, 2014;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, FKBP-rapamycin/rapalog complex mediated mechanism of mTOR function inhibition can be de facto the substantial source of the numerous off-target effects. FKBPs (of different molecular mass 12, 12.6, 13, 25, 51, and 52kDa) are the members of the family of peptidylprolyl cis/trans isomerases and strong binders of rapamycin Hausch et al, 2013). Besides their potential to form rapamycininduced ternary complexes with mTOR and hinder mTOR kinase substrate accessibility, the each member of this family has the diverse binding partners (Erlejman et al, 2014;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To specifically investigate the role of FKBP12 in the brain, Hoefner et al generated brain-specific FKBP12-deficient knockout mice [37]. An unexpected increase in mTOR pathway activity was observed, possibly due to a de-repressed, basal Akt signaling upstream of mTOR [38,39]. Brainspecific FKBP12 deletion also resulted in enhanced hippocampal longterm potentiation (LTP), one of the key molecular mechanisms for the formation of memory.…”
Section: Neuronal Functions Of Fkbpsmentioning
confidence: 95%
“…Recent evidence has also identified rapamycin/sirolimus as being the first drug to extend lifespan in a range of species from yeast to mammals 221,222 , highlighting the potential for drug targeting within this gene family to alleviate the ageing process. Importantly, recent studies have also shown that FK506-binding proteins can modulate Akt-mTOR signalling in the absence of rapamycin 21 .…”
Section: Ppiases As Targets To Prevent Ageing or To Treat Age-relatedmentioning
confidence: 99%
“…PPIases play a significant role by binding to and regulating the mTOR signalling pathway which has very well characterised roles in ageing and age-related diseases 21 . Furthermore, other PPIases such as CypA expression increases with ageing [30][31][32] and suppression of CypB induces cellular senescence 33 and its expression decreases in ageing rats 34 .…”
Section: The Role Of Ppiases In Agingmentioning
confidence: 99%
See 1 more Smart Citation